(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research aims to study the effect of Asset Quality on the financial performance of banks listed on Damascus securities exchange during the period from 2015 to 2020, using a sample consisting of 11 traditional private banks. Asset Quality was measured using non-performing loans to total loans, and the financial performance measured using return on assets. The results showed that there was no statistically significant effect of the quality of assets on the return on assets, while it was found that there was an inverse effect of the quality of assets on the return on assets after adjusting for the variable of size.